Disparity in Receipt and Utilization of Telecommunicator CPR Instruction. (3rd July 2020) - Amen, Amanda; Karabon, Patrick; Bartram, Cherie; Irwin, Kevin; Dunne, Robert; Wolff, Margaret; Daya, Mohamud R.; Vellano, Kim; McNally, Bryan; Jacobsen, Ryan C.; Swor, Robert; CARES Surveillance Group
Abstract : Introduction: Telecommunicator Assisted Cardiopulmonary Resuscitation (T-CPR) is independently associated with improved survival and improved functional outcome after adult Out of Hospital Cardiac Arrest (OHCA). The objective of this study was to evaluate whether there are racial and socioeconomic disparities in the provision of T-CPR instruction and subsequent CPR performance. Methods: We performed a retrospective review of a convenience sample of EMS agencies throughout the United States that utilized the Cardiac Arrest Registry to Enhance Survival (CARES) dispatch registry during the period 1/2014–12/2017. Data were collected by dispatch agencies after review of 9-1-1 OHCA audio recordings. Elements related to dispatcher CPR instruction, barriers to bystander CPR (BCPR) performance, patient race (White, Black, Hispanic-Latino, or other) and Utstein data were captured from the CARES database. These data were merged with census tract data from incident locations. The effects of race and income (Socioeconomic status, SES) on outcome were analyzed using multilevel logistic regression. Results: A total of 3, 807 cases were identified from 37 dispatch agencies in 6 states. The sample was predominantly White (57.5%) and male (64.9%) with an average age of 60.3 ± 19.9. In the adjusted analysis, there were no differences in the odds of receiving CPR instruction by race (black vs white), OR = 0.96 (95% CI. 0.70, 1.32) or for increased income, (OR = 1.00, 95% CI 0.99, 1.02). There was a significant difference in receipt of T-CPR instruction by patient age, OR = 0.99 (95% CI, 0.98, 0.99). Subsequent utilization of T-CPR instruction to perform BCPR was less likely for patients that had a lower income, OR = 1.03 (95% CI 1.01, 1.05). There was also a decreased rate of BCPR provision by patient age OR = 0.99 (95% CI, 0.99, 1.00), but there was no difference in rate of BCPR provision by race, OR = 0.86 (95% CI 0.61, 1.23). Conclusion: We identified differences in age but not race or SES in the provision of T-CPR instruction by dispatch centers. We also identified decreased CPR provision by age and income after receipt of T-CPR instructions. In this sample, we found no evidence of racial disparities in the provision of T-CPR instruction or subsequent provision of BCPR.